Visualisasi Mekanisme Flooding Aliran Counter-Current Air-Udara pada Simulator Hotleg Dengan L/D=50 - Suprianta Setiawan Putra; Apip Badarudin; De endarlianto; Indar to; Sinung Tirtha; Venti Yoanita; Marcellinus Sindhu (Retii, 2016)
In this study, the experiments used a hotleg simulator which consists of three parts: a horizontal pipe, bend and riser. Geometry sizes of pipes in a scale of 1/30 of the actual hotleg geometry size in the PWR, with ratio L/D = 50. Hotleg simulator has an inside diameter = 25.4 mm, the horizontal pipe length L = 1270 mm, and riser pipe length 20 mm with an angle of 50o. The visual data was collected by using a high speed camera to observe the mechanism of flooding that occurred in hotleg simulator. Flooding mechanism was identified by analyzing the phenomena that occur at the time of the flooding. From the observation of a high speed camera, it was found that the initiation of flooding coincided with the formation of liquid slug. At low superficial velocity of water, the onset of slugging occurs near a bend. While at higher superficial velocity of water, the onset of slugging occurs away from the bend.  Comparison of horizontal pipe length to the diameter of pipes (L/D) provide a significant effect on the flooding phenomenon.Keywords: pressurized water reactor, onset of flooding, onset of slugging, hydraulic jump, hotleg.